Media Pembelajaran Kongkrit Dalam Meningkatkan Motivasi Belajar IPA Siswa Kelas V SD YPK Sarawandori - Katulung, Marlin; Nurhartina, Andi; Sahara, Desy Putri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to determine the increase in science learning motivation through concrete learning media in fourth grade students of YPK Sarawandori Elementary School. This research is a classroom action research. The subjects of this study were fourth grade students with a total of 12 students. While the object of this research is students' science learning motivation after participating in learning by implementing concrete learning media. The data collection method used to collect data on students' science learning motivation is the questionnaire method. The data analysis technique used in this classroom action research is a quantitative descriptive analysis technique. The results of the study are evidenced by an increase in science learning motivation from the results of the questionnaire analysis in cycle I showing an average value of 67.5 with a percentage of completeness of 58%, increasing in cycle II with an average value of 88 and a percentage of completeness of 100%. Thus, these results indicate that concrete learning media can increase science learning motivation in fourth grade students of YPK Sarawandori Elementary School.